Implementasi Pengembangan Keberagamaan Peserta Didik Sekolah Menengah Atas (SMA) - Karlaely, Irma; Taufik Kurahman, Opik (Perkumpulan Peneliti dan Pegiat Literasi, 2024)
Religiosity in the context of Islamic religious education can be divided into vertical and horizontal dimensions. A vertical religious atmosphere can be realized through worship activities. On the other hand, a horizontal religious atmosphere links schools more as social institutions, which can be classified based on the structure of relationships between people. The school's efforts to improve students' religious attitudes are carried out through the implementation of Islamic activities. This research uses a literature review method, which involves researching literature and theories that are relevant to the problem being studied. The instrument used is descriptive analysis. Based on the results of the literature review analysis, the author will review it in detail in this article, discussing the implementation of student religious development in Senior High Schools (SMA). The implementation of religious diversity in high school students involves systematic efforts such as guidance, providing information, supervision and control. The aim is to improve the quality of students, especially in the religious aspect, in order to form a positive mental attitude and develop good potential. This aims to ensure that students' diversity can develop positively.